Cryptosporidiosis in Cattle and Buffaloes in Turkey - Molecular Analysis and Public Health Significance - Ertaş Oğuz, Fatma; Orunç Kilinç, Özlem; Ayan, Adnan; Yüksek, Nazmi; Burçak Aslan Çelik,; Gürkan Akyıldız,; ÖzgürYaşar Çelik, (Acta Scientiae Veterinariae, 2025)
Background: Calf diarrhea caused by infectious agents is one of the most significant and frequently encountered health problems in cattle breeding worldwide. Among these infectious agents, Cryptosporidium stands out as an important protozoan parasite, particularly affecting neonatal calves and young animals with immature or weakened immune systems. These early-life infections can lead to severe dehydration, weight loss, and even death if not properly managed. Cryptosporidium spp. is a zoonotic coccidian parasite known to play a substantial role in both human and animal health, especially in regions where hygiene and sanitation practices are inadequate. Its oocysts are highly resistant to environmental factors and common disinfectants, making control and prevention difficult. Importantly, due to its zoonotic nature, it poses a considerable threat to public health. This study was conducted to investigate the prevalence of cryptosporidiosis in buffaloes and cattle raised in the Van region using various diagnostic methods, and to evaluate its potential public health significance. Materials, Methods & Results: The fecal materials of the study were collected from 100 buffaloes and 200 cattle from different farms in Van province. The samples brought to the laboratory were stained with the Kinyoun Acid Fast method and DNA extraction was performed from each sample. Smear preparations were prepared from fresh fecal samples. The smear preparations were fixed in pure methanol for 1 min and allowed to dry, then stained in Kinyoun Carbol-Fuxin for 5 min, and then the slides were immersed in 50% ethyl alcohol, shaken, and immediately washed in tap water. The slides were placed in a decolorizing solution containing 1% sulfuric acid for 2 min and washed in tap water, then kept in a flask containing methylene blue for 1 min and washed again in tap water and left to dry. After drying, immersion oil was dripped and examined under a microscope at a magnification of 100x. DNA extraction was performed in all samples using a GeneMATRIX Stool DNA Purification Kit. Nested PCR analysis; Primers were used to amplify the SSU rRNA gene region of the obtained DNAs. In the PCR stage, 5’-TTCTAGAGCTAATA CATGCG-3’ and 5’-CCCATTTCCTTCGAAACAGGA-3’ primers were used to amplify the 1325 bp gene region. In the nested PCR stage, primers 5’- GGAAGGGTTG TATTTATTTATTAGATAAAG-3’ and 5’-AAGGAGTA AGGAACAACCTCCA-3’ were used to amplify the 826-864 bp gene region DNA extraction. The PCR products obtained were stained with RedSafe™ Nucleic Acid Staining Solution and images were obtained on 1.5% agarose gel. Positive PCR products were subjected to bidirectional sequencing at a commercial company (BM Labosis, Ankara, Turkey). As a result of microscopic and PCR analyses, 5.50% and 9.50% positivity were detected in cattle, 3% and 6% positivity in buffaloes, respectively. The infection prevalence was highest in cattle and buffaloes in the 0-6 month age group, 17.31% and 15.38%, respectively. In addition, zoonotic C. parvum was isolated from cattle calves. Discussion: In conclusion buffaloes and cattle, with their large fecal volumes, can easily contaminate the environment and serve as significant reservoirs for this pathogen, which is transmitted through water and food. Therefore, it is crucial to identify the Cryptosporidium species present in these animals. For this, epidemiological studies should be conducted and expanded with molecular methods. Keywords: calf, Cryptosporidium spp., protozoan, sequence analysis, zoonotic coccidian, neonatal enteritis, Van region.